A New Late Permian Burnetiamorph From Zambia Confirms Exceptional Levels of Endemism in Burnetiamorpha (Therapsida: Biarmosuchia) and an Updated Paleoenvironmental Interpretation of the Upper Madumabisa Mudstone Formation - Sidor, Christian A.; Tabor, Neil J.; Smith, Roger M. H. (Frontiers in Ecology and Evolution, 2021)
A new burnetiamorph therapsid, Isengops luangwensis, gen. et sp. nov., is described on the basis of a partial skull from the upper Madumabisa Mudstone Formation of the Luangwa Basin of northeastern Zambia. Isengops is diagnosed by reduced palatal dentition, a ridge-like palatine-pterygoid boss, a palatal exposure of the jugal that extends far anteriorly, a tall trigonal pyramid-shaped supraorbital boss, and a recess along the dorsal margin of the lateral temporal fenestra. The upper Madumabisa Mudstone Formation was deposited in a rift basin with lithofacies characterized by unchannelized flow, periods of subaerial desiccation and non-deposition, and pedogenesis, and can be biostratigraphically tied to the upper Cistecephalus Assemblage Zone of South Africa, suggesting a Wuchiapingian age. Isengops is the second burnetiamorph recognized from Zambia and is part of a tetrapod assemblage remarkably similar to others across southern Pangea during the Wuchiapingian. A revised cladistic analysis of Biarmosuchia yielded over 500 most parsimonious trees that generally reaffirm the results of previous analyses for burnetiamorphs: Lemurosaurus is basal, Lobalopex and Isengops are proximate burnetiid outgroups, and Bullacephalus, Burnetia, Mobaceras, Niuksenitia, and Pachydectes are burnetiines. Furthermore, Russian biarmosuchians are scattered throughout the tree and do not form sister taxon relationships with each other. Burnetiamorphs display a wide disparity of cranial adornments and are relatively speciose (13 species), especially when compared to the number of specimens discovered to date (~16 specimens). As has been suggested in some other tetrapod clades (e.g., ceratopsian dinosaurs), the burnetiamorph fossil record supports an inferred macroevolutionary relationship between cranial adornment and increased speciation rate.